Lost treasure of the emerald eye - Stilton, Geronimo (New York : Scholastic Inc., 2004)
The discovery of an old map by his sister Thea leads Geronimo and his family to search for buried treasure on a faraway island.
"English translation... by Edizioni Piemme S.p.a."--T.p. verso.
G3
Keywords: Mice -- Fiction; Journalists -- Fiction; Buried treasure -- Fiction; Islands -- Fiction; Adventure and adventurers -- Fiction; Humorous stories